Endoscopic repair of atrial functional mitral regurgitation in heart failure: long-term effects. (25th November 2020) - Balogh, Z; Mizukami, T; Bartunek, J; Collet, C; Beles, M; Albano, M; Katbeh, A; Casselman, F; Vanderheyden, M; Van Camp, G; Van Praet, F; Penicka, M
Abstract: Introduction: In patients with heart failure and preserved ejection fraction (HFpEF), even mild atrial functional mitral regurgitation (AFMR) has been associated with poor outcome. Objective: To describe long-term effects of endoscopic mitral valve (MV) repair on outcome in patients with HFpEF and AFMR. Methods: The study population consisted of consecutive patients with HFpEF (LVEF ≥50%, H2FPEF score ≥5) and AFMR, who underwent isolated, minimally invasive (endoscopic), MV repair (MVRepair group) (n=131) or remained on standard of care (StanCare group) (n=139). Patients with coronary artery disease or organic MR were excluded. Patients were matched using inverse probability of treatment weighting. Primary objective was all-cause mortality or HFpEF readmissions. Results: The median follow up was 5.03 years (IQR 2.6–7.9 years). In the MVRepair group, the perioperative, 30-day, 1- and 5-year mortality was 0, 1% and 12%, respectively. Additional 13 (10%) patients were readmitted for worsening HFpEF, while 2 (1%) individuals underwent redo MV surgery for recurrent MR. MVRepair compared with StanCare showed 21–29% (SE 6–8%) and 19–26% (SE 6–8%) absolute risk reduction of all-cause mortality and HFpEF readmissions, respectively (all p<0.05). MVRepair emerged as the strongest independent predictor of all-cause mortality (HR 0.16, 95% CI 0.07–0.34, p<0.001) and HFpEF readmissions (HR 0.21, 95% CI 0.09–0.51, p<0.001). At 5-year follow-up, in the MVRepair group, a total of 88% were alive and 80% were alive without readmission for HFpEF. Conclusions: Endoscopic MV repair is associated with low perioperative mortality, high long-term efficacy and appears to improve clinical outcome in patients with AFMR and HFpEF. Funding Acknowledgement: Type of funding source: None